Análise de antenas de microfita com patches circulares sobre substratos anisotrópicos usando o método dos potenciais de Hertz - Feitoza, Giordano Miranda (2005)
This work consists on the theoretical and numerical analysis of some properties of circular microstrip patch antennas on isotropic and uniaxial anisotropic substrates. For this purpose, a full wave analysis is performed, using Hertz Vector Potentials method in the Hankel Transform domain. In the numerical analysis, the moment method is also used in order to determine some characteristics of the antenna, such as: resonant frequency and radiation pattern. The definition of Hertz potentials in the Hankel domain is used in association with Maxwell´s equations and the boundary conditions of the structures to obtain the Green´s functions, relating the components of the current density on the patch and the tangential electric field components. Then, the Galerkin method is used to generate a matrix equation whose nontrivial solution is the complex resonant frequency of the structure. In the analysis, a microstrip antenna with only one isotropic dielectric layer is initially considered. For this structure, the effect of using superconductor patches is also analyzed. An analysis of a circular microstrip antenna on an uniaxial anisotropic dielectric layer is performed, using the Hertz vector potentials oriented along the optical axis of the material, that is perpendicular to the microstrip ground plane. Afterwards, the circular microstrip antenna using two uniaxial anisotropic dielectric layers is investigated, considering the particular case in which the inferior layer is filled by air. In this study, numerical results for resonant frequency and radiation pattern for circular microstrip antennas on isotropic and uniaxial anisotropic substrates are presented and compared with measured and calculated results found in the literature